Association between clinical outcomes and postoperative first metatarsal rotational alignment assessed by weight-bearing CT scan in hallux valgus - Prusmetikul, Suwimol; Orapin, Jakrapong; Vasaruchapong, Satetha; Tawonsawatruk, Tulyapruek; Jaovisidha, Suphaneewan; Manatrakul, Rawee; Tangkittithaworn, Phatthawit; Laohajaroensombat, Sukij (Frontiers in Surgery, 2025)
BackgroundThe significance of rotational deformity in the operative treatment of hallux valgus is growing. However, its impact on clinical outcomes remains inadequately explored. This study aims to investigate associations between residual rotational deformity and clinical outcomes following hallux valgus corrections.MethodsThis retrospective study analysed 47 postoperative feet, using WBCT to measure first metatarsal rotation via the α angle. The AOFAS Hallux MTP-IP, VAS-FA, and FAOS scores were assessed using this parameter.ResultsPatients with residual first metatarsal pronation demonstrated significantly poorer functions (84.14 ± 18.50; P-value = 0.04), other complaint subscales (78.78 ± 19.17; P-value = 0.03), and overall scores of the VAS-FA (82.93 ± 17.99; P-value = 0.04). A lower alignment subscale was observed in the AOFAS Hallux MTP-IP score (12.26 ± 3.49; P-value = 0.04), while other scales showed no significant differences between groups.ConclusionResidual first metatarsal pronation is associated with poorer clinical outcomes as shown by the overall score, function, and other complaint subscales of the VAS-FA, as well as the alignment subscale of the AOFAS Hallux MTP-IP. These findings underscore the importance of correcting rotational deformity for optimal results. Nonetheless, given the retrospective design of this study with only postoperative assessments, causal inferences regarding the role of residual pronation cannot be established and should be interpreted cautiously.